ANALISA URGENSI PERJANJIAN PRANIKAH SEBAGAI PERLINDUNGAN FINANSIAL PASANGAN DI ERA DIGITAL - Hamlatul Arsy Mulya; Fitria Agustin (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze the urgency of prenuptial agreements as financial protection for couples in the digital age. The method used is a qualitative approach with empirical legal methods. The results indicate that prenuptial agreements play a crucial role in providing legal certainty regarding asset management and debt responsibilities, as well as protecting couples from financial risks. However, in practice, obstacles remain, such as low legal awareness and social stigma. This study concludes that prenuptial agreements are an important instrument in preventing financial conflict in households in the digital age.